Exploring the learning theories underpinning in Technical, Vocational, Education and Training (TVET) curriculum perceived by TVET students - Hassan, Aminuddin; Lam, Kim Wai (Human Resource Management Academic Research Society, 2019)
The purpose of the study was to investigate students’ perceptions of level of knowledge about learning theories in the Technical and Vocational Education and Training (TVET) course possessed in one vocational college in Kuala Lumpur and one public institution in Selangor. Data were gathered from a sample of 69 and 171 TVET students using the paper-and-pencil Instruction Competency Questionnaire (ICQ) instrument. Percentage and frequency distributions were employed to analysis the data. Data were collected using a questionnaire administered to 171 randomly sampled TVET Students in Malaysia. Of those surveyed, 171 returned usable responses. Descriptive statistic was conducted to analyses the data. Of the respondents, 71.3% indicated that they have moderate low to low level of knowledge on behavioral, cognitive, and constructivist learning theories. The study also reported a need for students to increase their knowledge, especially, on constructivist learning theory, to empower them for taking charge of their own experiential learning to enhance their 21st century skills.